PROSES PRODUKSI KOPI SANTEN DI SURABAYA BARAT - ONNY PURNAMAYUDHIA ONNY YUDHIA; Ampar Jaya Suwondo; Bachtiar Rahman Halik (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2022)
The Community Service Program is a program that aims to provide training and assistance for SME partners, both in production and business management. After the survey was carried out, the Community Service Implementation Team collaborated with SME Partners. Santen Coffee "Tombo Kangen" in West Surabaya Region. The problems faced by SME Partners So far are the production results that have not increased and are only able to meet the needs of consumers in a limited market segment. The purpose of implementing this Community Service is so that SME Partners are able to increase their production results and improve welfare. The method implemented in this community service program is training and assistance in efficient and quality beverage processing which consists of providing cup sealers, making social media, making product labels and packaging, and preparing financial reports. The results of this community service are the use of a cup sealer tool, the business conditions per month have grown/increased, among others: the original production of 1,500 glasses of drinks to 3000 glasses of drinks, the original sales of Rp. 5.250.000,-/month has increased to Rp. 10.500.000,-/month. From a marketing perspective, there has been a change in the product marketing strategy, which was previously limited to the area of ​​West Surabaya, but is now outside the area.